2017
DOI: 10.1590/1807-1929/agriambi.v21n4p249-253
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical components and dry matter of lemon and mandarin hybrids under salt stress

Abstract: The objective was to study the biochemical changes and dry matter content in lemon and mandarin hybrids under salt stress during rootstock formation. For this, a study was conducted in randomized complete block, using a 2 x 5 factorial scheme, with two salinity levels (0.3 and 4.0 dS m-1) applied in five citrus rootstock genotypes (1. TSKC x CTARG - 019; 2. LRF; 3. TSKC x (LCR x TR) - 040; 4. LCRSTC and 5. LVK), with three replicates and four plants per plot. At 90 days after sowing, saline treatments started … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0
5

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 14 publications
1
5
0
5
Order By: Relevance
“…In addition, this effect on the pigments confirms the predominance of the osmotic effect because there was no effect on the contents of carotenoids, which are components considered as protectants, and tend to be high when there is a more severe stress condition, as observed by Sá et al (2017) in citrus plants. In this study, there were no effects of N doses on the contents of pigments; these results do not agree, partially, with those of Vieira et al (2010), who found increment in chlorophyll a but not in chlorophyll b, studying the effect of four N concentrations, through the addition or not of ammonium sulfate, on 'Pérola' pineapple plants.…”
Section: E Fsupporting
confidence: 55%
“…In addition, this effect on the pigments confirms the predominance of the osmotic effect because there was no effect on the contents of carotenoids, which are components considered as protectants, and tend to be high when there is a more severe stress condition, as observed by Sá et al (2017) in citrus plants. In this study, there were no effects of N doses on the contents of pigments; these results do not agree, partially, with those of Vieira et al (2010), who found increment in chlorophyll a but not in chlorophyll b, studying the effect of four N concentrations, through the addition or not of ammonium sulfate, on 'Pérola' pineapple plants.…”
Section: E Fsupporting
confidence: 55%
“…The increase of the biomass allocation in the "hard" jackfruit ( Figure 2B), may be an adaptation to the saline conditions imposed, since there is variability between varieties of the same species (PEREIRA et al, 2017;SÁ et al, 2017). As a defense mechanism, some varieties maintain high levels of potassium (K + ) and calcium (Ca 2+ ) and low sodium content (Na + ) in its tissues, thus absorbing higher amounts of K + + and Ca +2 , in order to maintain high K + /Na + and Ca 2+ /Na + ratios, so their biomass are not reduced even under saline conditions (GALDINO et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…These authors also state that root system inhibition occurs as a plant strategy to avoid contact with the salt present in the substrate. Most fruit trees present a detrimental effect on root growth with increased salt levels in the irrigation water, such as lemon (SÁ et al, 2017), papaya (LIMA NETO et al, 2016) and guava (OLIVEIRA et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…These authors still denote that the inhibition in the root system of the plant occurs as a strategy to avoid contact direct with the salt in the substrate. The majority of fruits presented a detriment in growth with increased salts in the irrigation water, such as lemon-Citrus limon (Sá et al, 2017), papaya (Lima Neto et al, 2016) and guava-Psidiun guajava (Cavalcante et al, 2010).…”
Section: Resultsmentioning
confidence: 99%